Hypothalamus and Post-Traumatic Stress Disorder: A Review - Payman Raise-Abdullahi; Morvarid Meamar; Abbas Ali Vafaei; Maryam Alizadeh; Masoomeh Dadkhah; Sakineh Shafia; Mohadeseh Ghalandari-Shamami; Ramtin Naderian; Seyed Afshin Samaei; Ali Rashidy-Pour (Brain Sciences, 2023)
Humans have lived in a dynamic environment fraught with potential dangers for thousands of years. While fear and stress were crucial for the survival of our ancestors, today, they are mostly considered harmful factors, threatening both our physical and mental health. Trauma is a highly stressful, often life-threatening event or a series of events, such as sexual assault, war, natural disasters, burns, and car accidents. Trauma can cause pathological metaplasticity, leading to long-lasting behavioral changes and impairing an individual’s ability to cope with future challenges. If an individual is vulnerable, a tremendously traumatic event may result in post-traumatic stress disorder (PTSD). The hypothalamus is critical in initiating hormonal responses to stressful stimuli via the hypothalamic–pituitary–adrenal (HPA) axis. Linked to the prefrontal cortex and limbic structures, especially the amygdala and hippocampus, the hypothalamus acts as a central hub, integrating physiological aspects of the stress response. Consequently, the hypothalamic functions have been attributed to the pathophysiology of PTSD. However, apart from the well-known role of the HPA axis, the hypothalamus may also play different roles in the development of PTSD through other pathways, including the hypothalamic–pituitary–thyroid (HPT) and hypothalamic–pituitary–gonadal (HPG) axes, as well as by secreting growth hormone, prolactin, dopamine, and oxytocin. This review aims to summarize the current evidence regarding the neuroendocrine functions of the hypothalamus, which are correlated with the development of PTSD. A better understanding of the role of the hypothalamus in PTSD could help develop better treatments for this debilitating condition.